Human collectin-11 (COLEC11) and its synergic genetic interaction with MASP2 are associated with the pathophysiology of Chagas Disease. - Thaisa Lucas Sandri; Fabiana Antunes Andrade; Kárita Cláudia Freitas Lidani; Elias Einig; Angelica Beate Winter Boldt; Benjamin Mordmüller; Meral Esen; Iara J Messias-Reason (Public Library of Science (PLoS), 2019)
Chagas Disease (CD) is an anthropozoonosis caused by Trypanosoma cruzi. With complex pathophysiology and variable clinical presentation, CD outcome can be influenced by parasite persistence and the host immune response. Complement activation is one of the primary defense mechanisms against pathogens, which can be initiated via pathogen recognition by pattern recognition molecules (PRMs). Collectin-11 is a multifunctional soluble PRM lectin, widely distributed throughout the body, with important participation in host defense, homeostasis, and embryogenesis. In complex with mannose-binding lectin-associated serine proteases (MASPs), collectin-11 may initiate the activation of complement, playing a role against pathogens, including T. cruzi. In this study, collectin-11 plasma levels and COLEC11 variants in exon 7 were assessed in a Brazilian cohort of 251 patients with chronic CD and 108 healthy controls. Gene-gene interactions between COLEC11 and MASP2 variants were analyzed. Collectin-11 levels were significantly decreased in CD patients compared to controls (p<0.0001). The allele rs7567833G, the genotypes rs7567833AG and rs7567833GG, and the COLEC11*GGC haplotype were related to T. cruzi infection and clinical progression towards symptomatic CD. COLEC11 and MASP2*CD risk genotypes were associated with cardiomyopathy (p = 0.014; OR 9.3, 95% CI 1.2-74) and with the cardiodigestive form of CD (p = 0.005; OR 15.2, 95% CI 1.7-137), suggesting that both loci act synergistically in immune modulation of the disease. The decreased levels of collectin-11 in CD patients may be associated with the disease process. The COLEC11 variant rs7567833G and also the COLEC11 and MASP2*CD risk genotype interaction were associated with the pathophysiology of CD.